PENGARUH KESIAPAN BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM KELAS IX DI SMPN 2 UKUI - Agus Rifai; Risnawati; Granita (STKIP Subang, 2025)
This study aims to show and prove whether there is a significant influence between learning readiness and learning motivation simultaneously and partially on learning outcomes in Islamic Religious Education subjects at SMP Negeri 2 Ukui. This type of research is quantitative research. The data collection technique used is a questionnaire to measure the level of learning readiness and learning motivation and report card scores to measure learning outcomes. The analysis technique used is multiple linear regression with the help of SPSS version 27.00. The results of the study indicate a significant influence between learning readiness and learning motivation on learning outcomes. This is indicated by the F count value of 47.021 with a significance of <0.001 compared to F table of 2.76. Thus, it is concluded that 47.021 > 2.76 proves that there is a significant influence between learning readiness and learning motivation on student learning outcomes in Islamic Religious Education subjects at SMP Negeri 2 Ukui.